Measuring Worker Protection Using Leximetrics: Illustrating a New Approach in Four Asia-Pacific Countries. (28th November 2019) - Mahy, Petra; Mitchell, Richard; Sutherland, Carolyn; Gahan, Peter; O'Donnell, Anthony; Cooney, Sean; Anderson, Gordon; Mao, Lingfeng; Stewart, Andrew
Abstract: This Article introduces the Worker Protection Index (WPI), a new measure for quantitative cross-national comparison of the strength of worker protection provided by law. After presenting an overview and critique of existing labor regulation indices, the Article outlines the conceptual and methodological innovations used in order to develop the WPI. The WPI is wider in scope than many other comparable indices and arguably is more sensitive to variance in labor regulation systems around the world. We then briefly present some initial coding results for Australia, China, Indonesia, and New Zealand, illustrating the impact of our innovations by contrasting these findings with the Cambridge Centre for Business Regulation (CBR) Labour Regulation Index (LRI).